TRADISI NGUNJUNG BUYUT NYI MAS ENDANG GEULIS PENGAMPON DESA DANAWINANGUN KECAMATAN KLANGENAN KABUPATEN CIREBON (KAJIAN LIVING HADIS) - Lestari, Dinda; Hartati, Hartati; Iskandar, Amin (Universitas Islam Negeri Siber Syekh Nurjati Cirebon, 2024)
The tradition of visiting Nyi Mas Endang Geulis' great-grandfather is an annual traditional ceremony held by the Pengampon community of Danawinangun village, Klangenan, Cirebon. This tradition aims to honor and commemorate the services of ancestors, especially Nyi Mas Endang Geulis, who is considered an important figure in local history and culture, by visiting petilasan (a place believed by the community to be the place where Nyi Mas Endang Geulis once visited) to pray for him together. Departing from this background, the researcher was interested in researching more deeply about